#TITLE_ALTERNATIVE# - MOCHAMAD GUS NURULLAH (NIM 13202186), MAS
Orthogonal Frequency Division Multiplexing (OFDM) is a multicarrier modulation technique that recently has been adopted widely for high data rate communication systems like Digital Subscriber Lines (DSL), Wireless LAN (802.11 a/g/n), Digital Video Broadcasting and WiMAX. Basic principle of OFDM is to divide high speed serial data into a number of low speed paralel data that transmitted simultaneously through a number of subcarrier thus having longer simbol duration. This characteristic make OFDM has some advantages to combat frequency selective fading on multipath channel and can eliminate almost completely intersymbol interference (ISI). Beside its advantages, OFDM also has some disadvantages. One major drawback is the problem of PAPR (Peak to Average Power Ratio). PAPR constitute power variation in OFDM that can be defined as ratio between maximum signal power and mean signal power in a spesific time duration. High PAPR increases complexity of ADC and DAC and also reduce HPA eficiency. Tone Reservation (TR) is one of an eficient PAPR reduction techniques because can be implemented with low complexity. TR can reduce PAPR by reserve small part of subcarriers so there is a small data rate loss. Reduction process in TR work in time domain. From the simulation result, TR technique can achieve 4.95 dB PAPR reduction with only use of 10% of subcarriers. Beside it, this technique can give BER performance increase for 6 dB and 8 dB amplifier IBO (Input Backoff).